Diversity, Distribution and Abundance of Solanaceae Family Species at Ngel-Nyaki Forest Reserve, Taraba State, Nigeria. - Duru, C. E.; D. Kulawe (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY (2536-6041), 2023)
Solanaceae or nightshades are a family of flowering plants that ranges from annual and perennial herbs to vines, lianas, epiphytes, shrubs and trees (Watson and Dallwitz, 1992). Family Solanaceae include a number of agricultural crops, medicine plants, weeds, spices and ornamentals (Heiser, 1969). Common fruits of Solanaceae family includes: tomatoes, eggplant, bell peppers and chili peppers, all of which are closely related and are use as food in the world today (Balken, 2016). Despite the economic importance of the Solanaceae family in the world today, their diversity, distribution and abundance of its species in Ngel-Nyaki Forest Reserve cannot be fully assessed. Hence the research aimed at assessing the diversity, distribution and abundance of Solanaceae species at the forest reserve. A study was carried out at Ngel-Nyaki Forest Reserve of Taraba state, Nigeria to assess the diversity, distribution and abundance of species of Solanaceae across the protected and unprotected areas of the reserve. Fourteen plots measuring 100x 50m were established after a pilot study was done to establish the positions where species of Solanaceae occurred in the reserve. In each plot, the various Solanaceae species encountered where identified and counted. 143 individuals were sampled and fourteen species were identified. Result from the study revealed that species abundance and diversity was highest in the unprotected area when compared to the protected area and this could be as a result of soil factor (such as soil mineral and soil type), grazing activities by cattle which aid seed dispersal activities and cattle dung which serves as organic manure. The study confirms that Solanaceae species are important species for conservation and regeneration, due to their economic and medicinal value they provide.